Stakeholders' Perceptions of Science-Day Programs at University-Based Science Outreach Centers. Issue 2 (3rd July 2019) - Nativ Ronen, Efrat; Tal, Tali
Abstract: University-based science youth centers offer science-day activities for students that include lectures and sometimes a laboratory experience. This phenomenological study explores stakeholders' views of science-day programs at 3 different university-based science outreach centers. The study describes the characteristics, the goals, the pedagogy, and the challenges of science days as voiced by the different informants. We found that the main goal was exposing students to science and "showing STEM is fun." Some teachers sought added value of learning in out-of-school environments and pointed to the importance of hands-on activities. The centers' staff did not address pedagogy and viewed teachers' role as being chaperons. Teachers felt patronized by the young guides who did not acknowledge their experience and expertise. Some differences in approaches of junior and senior teachers are discussed. In conclusion, we recommend mutual discussion of goals, and finding ways for teachers and centers' staff to collaborate in planning and enactment of science days.